Book Review: Islamicity Indices, The Seed for Change - Riani, Ririn (Islamic Economics Methodology, 2025)
The book Islamicity Indices: The Seed for Change by Hossein Askari and Hossein Mohammadkhan (2016) introduces a quantitative framework to measure the extent to which countries apply Islamic values in their social, economic, and political practices. Through five main indices—economic, legal and governance, human and political rights, international relations, and an overall index—the authors reveal that many non-Muslim countries are precisely more "Islamic" in their implementation of the values of justice, transparency, and social welfare than countries with majority-Muslim populations. This study affirms the need for structural and ethical reforms so that the Muslim world can return to the principles of justice and universal welfare as taught by the Qur’an and exemplified by Prophet Muhammad PBUH.